Guidance for Processing Fresh Juices in Retail Operations - Keith R. Schneider; Victor Garrido; W. Steve Otwell; Ray Mobley (EDIS)
Juice is defined in 21 CFR 120.1; "juice"' refers both to beverages that are composed exclusively of an aqueous liquid or liquids extracted from one or more fruits or vegetables and to the juice ingredient in those beverages that contain other ingredients in addition to juice. In this guidance, the term "juice product" refers both to beverages that contain only juice and to the juice ingredient of beverages that are composed of juice and other ingredients. Fresh juice is defined as a juice product that has not been subjected to a process, such as pasteurization, to prevent, reduce or eliminate microbiological hazards. This document is FSHN05-06, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. Published: February 2005.